The International Monetary Fund and the Private Markets - Witteveen, H. J.; Group of Thirty (New York (Two World Trade Center, Suite 9630, New York 10048) : The Group, 1983)
This study suggests that the International Monetary Fund may soon need to borrow from private financial markets for the first time, to obtain supplementary bridging finance until new resources are made available under the recent agreements to enlarge general quota subscriptions and the General Arrangements to Borrow.
Cover title: The IMF and the private markets.
rua 19/06/17
Loans.
Keywords: Financial institutions, international; International Monetary Fund